Plan de negocio para la creación de una empresa de organización de eventos sociales en la ciudad de Santa Marta. - Ardila Castrillòn, Jessica Lorena (Universidad Antonio Nariño, 2023)
The business plan is the organized idea of the start-up of a company dedicated to the organization of social events in a business and daily panorama, in addition to that it allows the experimental part of a real market study using the knowledge acquired; This through the implementation of a methodology based on the description and quantification of sample data or populations, the efficient solution of this project not only guarantees learning in academic matters; if not, it opens the way to the near possibility of implementing a process that benefits the community with the generation of employment and the satisfaction of an existing demand. For this reason, this research highlights the development of the constitutive elements of a business plan from the identification of the respective market study and the development of technical and financial studies together with the role of marketing as part of the business strategy for the determination of promotion strategies and identification of the target market, from which the viability of this business plan has to be concluded by quantifying the costs and revenues, that reward the profitability of the same and its permanence in the market of Santa Marta, as sustainability, as indicated in the development of the approaches presented.